Bioaktivitas Ekstrak Etil Asetat Hasil Fermentasi Fungi Endofit Batang Bajakah (Uncaria nervosa Elmer.): Bioactivity of Ethyl Acetate Extract from Fermentation of the Endophytic Stem of Bajakah (Uncaria nervosa Elmer.) - Khoirunnisa Khoirunnisa; Novianty Indjar Gama; M. Arifuddin; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Uncaria nervosa Elmer. or commonly known as Bajakah is a plant endemic to Kalimantan which is believed to treat cancer. Utilization of endophytic fungal microorganisms is an effort to maintain the sustainability of plants that have the ability to transfer genetics from their host plants. The aims of this study were to determine the amount of yield, to obtain the types of secondary metabolites contained in the ethyl acetate extract, and to determine the toxicity of endophytic fungi isolates based on LC50 values for Artemia salina larvae. The methods used were isolation of endophytic fungi, endophytic fungi extraction, phytochemical tests using TLC and cytotoxic testing using the Brine Shrimp Lethality Test (BSLT) method using Artemia salina larvae as test animals. The total yield of isolate G1A1 and isolate G1A3 were 0.0084% and 0.0078%, respectively. The results of the phytochemical screening of isolate G1A1 were tannins (Rf = 0.55) and triterpenoids (Rf = 0.6). Isolate G1A3 contains triterpenoids (Rf = 0.5) and flavonoids (Rf = 0.9). The LC50 value of isolate G1A1 was 512.86 ppm and isolate G1A3 was 660.7 ppm which has the potential to be cytotoxic. Keywords: endophytic fungi, TLC, BSLT Abstrak Uncaria nervosa Elmer. atau biasa dikenal dengan Bajakah merupakan tanaman endemik Kalimantan yang dipercaya dapat mengobati kanker. Pemanfaatan mikroorganisme fungi endofit menjadi upaya dalam menjaga keberlangsungan tumbuhan yang memiliki kemampuan transfer genetik dari tanaman inangnya. Tujuan dari penenlitian ini adalah mengetahui jumlah rendemen, mendapatkan jenis metabolit sekunder yang terkandung dalam ekstrak etil asetat, dan mengetahui toksisitas isolat fungi endofit berdasarkan nilai LC50 terhadap larva Artemia salina. Metode yang digunakan adalah isolasi fungi endofit, ekstraksi fungi endofit, uji fitokimia dengan KLT dan pengujian sitotoksik dengan metode Brine Shrimp Lethality Test (BSLT) menggunakan hewan uji dari larva Artemia salina. Jumlah rendemen isolat G1A1 dan isolat G1A3 masing-masing sebesar 0,0084% dan 0,0078%. Hasil skrining fitokimia isolat G1A1 adalah tanin (Rf = 0,55) dan triterpenoid (Rf =0,6). Pada isolat G1A3 mengandung triterpenoid (Rf = 0,5) dan flavonoid (Rf = 0,9). Nilai LC50 isolat G1A1 sebesar 512,86 ppm dan pada isolat G1A3 sebesar 660,7 ppm yang berpotensi sebagai sitotoksik. Kata Kunci: fungi endofit, KLT, BSLT